The Effect of Ethanolic Extract of Cashew Fruit Peel on The Liver Histological Structure in Rat (Rattus norvegicus Berkenhout, 1769) - Laili Mufli Zusrina; Bambang Retnoaji; Nastiti Wijayanti (Universitas Gadjah Mada, 2019)
Cashew fruit peel is a waste produced from the cashew nut industry, and it has not been utilized optimally yet. Cashew peel extract has the potential to be used as a contraceptive agent, which capable of reducing reproductive capacity. However, its side effects on other tissue and organ such as liver not clearly studied yet. This study aims to determine the effect of ethanolic extracts of cashew peel on the histological structure of the white rat liver. In this study, 21 female white rats were used and be grouped for control (6 mice) which were treated with CMCMa 0.5% and 15 mice were treated with peel extract of 500 mg/kg body every day for one month. Liver for examination was collected sequentially at 3rd, 5th, 8th, 11th, and 14th of the estrous cycle. The liver was processed for histological observation and stained with Hematoxylin Eosin and Mallory Acid Fuchsin staining solution. The liver hepatocyte was observed for it abnormality and be scored to calculate the number of cell damage or abnormality. The result showed that peel extract-treated mouse liver was similar to control ones; we did not witness any evidence of fibrosis, pyknosis and cellular necrosis on either control or treated mouse. Statistical analysis by SPSS showed that the p-value between the control and treatment groups was 0.078 (> 0.05) so there was no significant difference between control and treatment. It could be concluded that ethanolic extracts of cashew nuts peel with a concentration of 500 mg/kg body weight caused no effect on the mouse liver histological structure. application with reduced-dosages of NPK fertilizers were arranged in a random block design with three replicates. The results show that large quantities of silica bodies attached to the surface of EFB fibers and amounting to 0.44% soluble Si. The FFB data indicated that the application of 75% NPK + 500 kg composted EFB + 2 L BioSilAc/ha/year on a five-year-old plant resulted in higher yield than that obtained from 100% standard dosage of NPK. The study also revealed that the application of EFB compost reduced 50% of BioSilAc dosage.